Variatión morfológica de los peces Hemibrycon boquiae y Hemibrycon rafaelense (Charatiformes: Characidae) en el Rió Cauca, Colombia. - Román-Valencia, César; Arcila-Mesa, Dahiana K.; Hurtado, Hernando T. (Revista de Biología Tropical, 2009)
We analyzed the variation in morphological and osteological characteristics of Hemibrycon boquiae and Hemibrycon rafaelense in the Cauca River. The multivariate analysis determined populations of H. boquiae in nine streams: Boquier, Honda, Las Aguilas, Doña Juana, Villa Paola, Portachuelo, The Snake, Aimes and Ramirez, and populations of H. rafaelense in four streams: Canceles, Clara, San Rafael and San Jose. There were morphometric differences among populations of H. boquiae (n= 277) and H. rafaelense (n= 121). Nevertheless, there were significant meristic discrepancies among populations of both species: number of scales between lateral line and anal fin, and number of scales between lateral line and pelvic fin. The absence of bilateral symmetry was observed in the number of maxillary teeth in H. boquiae. The cluster analysis distance for osteological characters, including the number of predorsal scales, separated H. boquiae and H. rafaelense in two defined groups.